Hospital governance accountability structure: a scoping review - Mohammad Ali Jalilvand; Ahmad Reza Raeisi; Nasrin Shaarbafchizadeh (BMC, 2024)
Abstract Introduction Hospitals, as complex organizations with clinical, financial, and social functions, face different barriers to providing high-quality and safe services at reasonable costs. Various initiatives have been carried out in hospital governance to improve quality, safety, and accountability. This research aims to identify the structures and dimensions that make hospital governance accountable. Methods The research used Arksey and O'Malley's scoping review framework to examine the research literature on hospital governance structure and accountability. The literature review included PubMed, Web of Science, Embase, Scopus ProQuest, Google search engine, and Google Scholar databases from 2010 to 2023. Data were analyzed using the content analysis method. Results Excluding unrelated and duplicate sources, 40 articles and reports were included in the study. The studies were reviewed and analyzed based on organizational type, type of source, year of publication, objectives, and key findings. Accountable governance features were extracted from the selected articles and reports. The four main themes include inclusive governance, commitment to accountability, planning for accountability, and autonomous governance. Thirteen subthemes were extracted from the study literature. Conclusion Various initiatives have been implemented regarding the reform of the governance structure of public hospitals in different countries. Many of these reforms aim to improve financial and clinical accountability. The study results could be used to identify the structures and dimensions that make hospital governance accountable.